ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN TRANSPORTASI DARAT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Zikra Aditya Rifqi; Mariaty Ibrahim (Bisnis-Net, 2023)
One way that can show how a company's financial performance is good or not, namely by analyzing financial statements consisting of the ratio of likidity, solvency, profitability and activity. By obtaining the value of the ratio, it can measure the financial performance of the company that is being run. This study aims to determine the financial performance of land transportation companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. This study used quantitative-descriptive analysis method. Data analysis techniques use analysis of financial ratios (liquidity, solvency, profitability and activity). The results of this study show that the liquidity ratio is not good, solvency is not good, profitability is not good and activity is good so that the company's financial performance is declared less good.